An Up-To-Date View at the Etiopathogenesis of Keratoconus - Hilmi Or (Türk Oftalmoloji Dergisi)
The etiology of keratoconus is unknown. Different factors have been shown to play a role in the etiology and pathogenesis. Both genetic and environmental factors are thought to play a role in the formation of the disease. The research studies that have been done so far suggest a multifactorial phenotypic expression. Research studies have been conducted to find the possible genetic factors for keratoconus in various aspects: Analysis of diseases coexisting with keratoconus, gene research, protein and enzyme studies are some of the studies in this direction. Recent research in the pathophysiology of keratoconus on the basis of cell has shown oxidative stress as a cause of ectatic changes. In the etiology apart from genetic factors, hormones and hormonal balances are investigated, as well as chronic trauma (contact lens use and eye rubbing) is examined as a possible cause. (Turk J Oph thal mol 2011; 41: 339-47)